Menganalisis Layanan Kunjungan Rumah, Advokasi, dan Konferensi Kasus dalam Pelaksanaan Bimbingan dan Konseling - Rachmawati, Amalia Putri; Jannah, Ilda Miftakhul; Putri, Abrillianty Tivany Surya; Rusty, Fisya Aulia; Christiana, Elisabeth (TSAQOFAH, 2025)
Guidance and Counseling (BK) plays a vital role in supporting the development of students, especially in overcoming personal, social, academic, and career problems. One important component of BK services is supporting activities such as home visits, advocacy, and case conferences. Home visits aim to understand the conditions of students' families in depth and build cooperation with parents, so that solutions to problems faced by students can be optimized. Advocacy functions to accompany students who face unfair or discriminatory treatment, with a focus on restoring their rights. Case conferences, as a discussion forum involving various related parties, play an important role in finding the best solutions to student problems collaboratively and confidentially. These three services complement each other, providing comprehensive support in overcoming student problems, and building stronger relationships between schools, families, and communities in achieving optimal educational goals. This study uses a qualitative approach with a literature study to analyze the role and implementation of these three services in the context of implementing Guidance and Counseling.